New harmony of Javanese keroncong case study: Boogie Rahayu's work on the Kroncwrong album Sono Seni Ensemble - Zulkarnain Mistortoify; Bao Hanshi (International Journal of Visual and Performing Arts, 2023)
This research aims to unveil one of the compositional works of the Sono Seni Ensemble Surakarta music group, titled 'Boogie Rahayu.' This work offers a distinct paradigm and compositional technique in comparison to the works of typical progressive keroncong orchestra groups. The study endeavors to reveal the composition of 'Boogie Rahayu' through an analysis that integrates source knowledge of karawitan music structures, keroncong playing techniques, attitudes towards sound sources, and an openness to presenting new harmonies. Examining this compositional work contributes to addressing the issue of creativity stagnation in the Javanese style of keroncong. The research adopts a musicological and cultural approach, focusing on the primary objects of the work and the performers. Data collection techniques involve field observations and interviews conducted through both online and offline methods, as well as document and artifact studies using conventional and online methods. During the analysis stage, this study employs an emic approach, considering the composer's thoughts and beliefs, alongside a musicological approach that delves into musical structure, rhythm changes, cadence interpretation, and chord harmony. The results of the research indicate that 'Boogie Rahayu' introduces a new avenue of development capable of transcending artistic and aesthetic boundaries among keroncong music, Javanese style, and Javanese karawitan